Biosimilar infliximab administration for the management of acute graft-versus-host disease. (December 2020) - Tollkuci, Eris; Fitzpatrick, Paul; N Seddon, Amanda; Myers, Rebecca; Nathan, Sunita; Ustun, Celalettin
Introduction: Acute graft-versus-host disease (aGVHD) is a significant immune-mediated complication of allogeneic hematopoietic stem cell transplant (HSCT). Despite prophylactic immunosuppression, the incidence of grades II–IV aGVHD post-HSCT varies from 20 to 80%. Tumor necrosis factor (TNF) is an important cytokine involved in the pathogenesis of GVHD, and medications such as infliximab (Remicade®) have been utilized as second-line treatment options in patients with steroid-refractory GHVD. Infliximab-dyyb (Inflectra®) and infliximab-qbtx (Ixifi®) are biosimilars approved by the FDA for a variety of autoimmune disorders. This is the first case report documenting the utility of infliximab-dyyb and -qbtx for the management of steroid-refractory aGVHD. Case report: We report the post-transplant course of three patients treated with infliximab biosimilars as a part of therapy for management of steroid-refractory aGVHD. Management and outcome: Steroid-refractory aGVHD is associated with poor prognosis and its management, as highlighted in our three patient cases, and can be very diverse often requiring different therapeutic modalities which overlap in administration. Discussion: In these patients with steroid-refractory aGVHD, we were able to show that infliximab biosimilars could be used in lieu of the reference infliximab product. Although we had important limitations, this case report supports the use of anti-TNF agents in highly mortal steroid-refractory acute GI GVHD and that replacement of infliximab with its biosimilars is feasible.